2019
DOI: 10.1007/s42452-019-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

PIV measurement and CFD simulations of an air terminal device with a dynamically adapting geometry

Abstract: Air quality is an important factor for human well-being, and it is crucial that when using mechanical ventilation system, air is properly distributed so it reaches every user of a ventilated zone. To improve ventilation systems, and in consequence the air quality, this paper focuses on studying the impact of an air terminal device (ATD) with a dynamically changing geometry on the effectiveness of a variable air volume (VAV) ventilation system. VAV system characterizes a change in the airflow magnitude through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Long-term exposure to a high concentration of air pollutants causes illness and affects the comfort of work for occupants, and, to ensure human safety and health, the air exchange rate should be adjusted, providing that the outside air is less polluted than indoor air [27]. With additional factors, such as ventilation methods, occupant contribution, and faulty equipment, that have been proven to influence the air quality in previous studies [28][29][30], it is important to make sure that, when using solid fuel, the indoor air quality is not degraded even more by its operation.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to a high concentration of air pollutants causes illness and affects the comfort of work for occupants, and, to ensure human safety and health, the air exchange rate should be adjusted, providing that the outside air is less polluted than indoor air [27]. With additional factors, such as ventilation methods, occupant contribution, and faulty equipment, that have been proven to influence the air quality in previous studies [28][29][30], it is important to make sure that, when using solid fuel, the indoor air quality is not degraded even more by its operation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed that the best air quality was when the air freely flowed through the garage door and no gasket was used. To improve ventilation systems and, in consequence, the air quality, Nina et al [24] also focused on studying the impact of an air terminal device (ATD) with a dynamically changing geometry on the effectiveness of a variable air volume (VAV) ventilation system using CFD. The results of the simulations and the PIV measurements showed that the changes in the geometry of the air terminal device improve the ventilation effectiveness of a VAV system, allowing the system to maintain a constant air throw despite the changing airflow magnitude through the system.…”
Section: Introductionmentioning
confidence: 99%
“…Zhiyi et al [16] investigated ventilation performance in typical apartment buildings predicted by CFD in a multi-zone airflow model. The improvement in indoor air quality (IAQ) was also conducted by the measurement and CFD simulations that are shown as valid tools for IAQ indication [17]. In addition, CFD modeling of contaminant migration in a household gas furnace was investigated by Szczepanik-Scislo [18].…”
Section: Introductionmentioning
confidence: 99%